Adaptation Patterns of the Berbers in Morocco and Algeria: Julian Steward's Cultural Ecological Perspectives - Zulfa, Rafika Fidlaty (Middle Eastern Culture & Religion Issues, 2022)
The relationship between the environment and humans is not one-way. How humans adapt to their environment affects the culture and environment that will be formed in the region. Berber which is one of the largest ethnic groups in the Middle East, especially North Africa, has a unique and diverse pattern of adaptation. This paper focuses on research on the adaptation pattern of the Berbers in the two regions with the largest populations, namely Algeria and Morocco. Viewed from the perspective of Julian Steward's cultural ecology, the Berber tribe which is synonymous with nomadic and herding habits is a form of environmental adaptation in the Sahara desert, while trading and farming is a form of adaptation of the Berber tribes who live and settle in the Rifs mountains in Morocco and some hilly valleys such as Kabylie , Aures, and M'azb in Algeria. The results showed that herding, nomads, exploring water holes in the desert, navigating the stars, making tents and clothes from wool and sheepskin were the result of the adaptation of the Berbers to the environment they inhabited.